Mental-Emotional Disorder, Fear and Depression Level of Emergency Nurses During Pandemic Covid-19: A Comparative Study - Marliana, Thika; Kurniawati, Indah; Jamiatun, Jamiatun; Safitri, Yeni (GLOBAL HEALTH SCIENCE GROUP, 2024)
Emergency nursing is specialized nursing that focuses on care that requires immediate medical attention to avoid long-term disability or death. During the COVID-19 pandemic, emergency nurses are on the front lines and must be prepared, and must be able to sort and select patients safely. However, emergency nursing services are very risky in transmitting exposure to the COVID-19 virus. This study aims to assess and compare the levels of mental and emotional disorders, depression, and anxiety suffered by emergency room nurses in the Intensive Care Unit, Operating Room, and Emergency Room. In this comparative study, we collected data from 92 nurses using a cross-sectional correlation design. In addition to the Sociodemographic Characterization, Psychoemotional Disorder Scale, Depression Scale, and COVID-19 Anxiety Scale. Levels of depression were higher in operating room nurses than in the intensive care unit and emergency room nurses (54.17 ± 14.08 vs 48.53 ± 11.92, p<0.01). (48.36 ± 13.40 vs 45.74 ± 11.79, p < 0.01). The pandemic is having a significant impact on the mental health of emergency room caregivers. New specific support measures should be formulated. More research is needed to focus on the psychological resilience of emergency department nurses.